Nonlinear perturbations of systems of partial differential equations with constant coefficients - Carmen J. Vanegas (Electronic Journal of Differential Equations, 2000)
In this article, we show the existence of solutions to boundary-value problems, consisting of nonlinear systems of partial differential equations with constant coefficients. For this purpose, we use the right inverse of an associated operator and a fix point argument. As illustrations, we apply this method to Helmholtz equations and to second order systems of elliptic equations.